2022
DOI: 10.1186/s13287-022-03167-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia-preconditioned HucMSCs on neovascularization and follicle survival in frozen/thawed human ovarian cortex transplanted to immunodeficient mice

Abstract: Background The massive loss of follicles in the early stage of ovarian tissue transplantation is considered a significant restriction to the efficacy of ovarian tissue cryopreservation (OTC) and transplantation (OT). The use of mesenchymal stem cells (MSCs) before transplantation of ovarian fragments shortened the hypoxic period and boosted neovascularization. Hypoxia-preconditioned MSCs can enhance the potential of angiogenesis. Can hypoxia-preconditioned human umbilical cord mesenchymal stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…CD31 plays a crucial role in in ammation, immune response and angiogenesis, and is involved in endothelial cell migration, cell connection development and homeostasis, and capillary formation [27,28]. MSCs can actively protect transplanted tissues by increasing higher expression of CD31, CD34, and VEGFA for early angiogenesis [29].Our results suggest that MSCs in TTT accelerate wound healing by promoting the expression of CD31 in neovascularization and new skin.…”
Section: Discussionmentioning
confidence: 76%
“…CD31 plays a crucial role in in ammation, immune response and angiogenesis, and is involved in endothelial cell migration, cell connection development and homeostasis, and capillary formation [27,28]. MSCs can actively protect transplanted tissues by increasing higher expression of CD31, CD34, and VEGFA for early angiogenesis [29].Our results suggest that MSCs in TTT accelerate wound healing by promoting the expression of CD31 in neovascularization and new skin.…”
Section: Discussionmentioning
confidence: 76%
“…The hypoxic HUC-MSCs exhibited notable protection against apoptosis within the graft tissues. Additionally, they stimulated the upregulation of CD31, CD34, and VEGF genes, facilitating efficient and prompt angiogenesis (32).They also protect and preserve ovarian follicles by inducing changes in follicular death. Previous research on the effects of umbilical cord MSCs that were grafted with OT, 48 hours before grafting under hypoxic conditions showed anti-apoptotic, angiogenic, and protective effects on ovarian reserves (32) Based on the findings mentioned earlier, our research revealed that despite nonhypoxic cell culture conditions, the HUC-MSCs exhibited comparable anti-apoptotic, angiogenic, and protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…After being cryopreserved by a slow-freezing procedure and subsequently thawed, ovarian tissue fragments were transplanted to SCID or BALB/c mice. Grafting sites differed between studies, ranging from orthotopic intraperitoneal transplantation to heterotopic graft positioning under the renal capsule, subcutaneously, or into the back muscle region [20][21][22][23]. Two studies used commercially acquired human ASCs and performed a two-step procedure.…”
Section: Experimental Design Of Included Studiesmentioning
confidence: 99%
“…They preconditioned their human umbilical cord mesenchymal stem cells (hUC-MSCs), predicting that a hypoxic environment will enhance proangiogenic factor secretion. The hUC-MSCs were placed in a hypoxic incubator with only 3% O 2 for 48 h before transplantation [20].…”
Section: Experimental Design Of Included Studiesmentioning
confidence: 99%